Quality of Life in Jail: gender, Correlates, and Drivers in a Carceral Space - Prost, Stephanie Grace (International journal of offender therapy and comparative criminology, 2020)
Quality of life (QOL) is an important area of exploration in U.S. corrections linked closely to well-being and an important indicator of intervention efficacy. Little is known of QOL in U.S. jails despite the admittance of over 10-million people to these settings every year. Research regarding the dimensions, correlates, and gender disparities in QOL in jails is important to shaping gender-responsive supports and reducing recidivism. Independent t tests and correlational and regression analyses were used to explore dimensions, correlates, and gender disparities in QOL among persons incarcerated in a large, southeastern jail (N = 299). All QOL domains were significantly related to overall QOL, and psychological QOL contributed most readily to respondent’s overall QOL. Females, on average, reported lower QOL than males with significant differences between the groups in physical health and psychological domains. The importance of psychological QOL intervention and healthcare continuity are discussed.